2010
DOI: 10.1073/pnas.1003547107
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning beyond retinotopic reference frame

Abstract: Repetitive experience with the same visual stimulus and task can remarkably improve behavioral performance on the task. This wellknown perceptual-learning phenomenon is usually specific to the trained retinal-or visual-field location, which is taken as an indication of plastic changes in retinotopic visual areas. In previous studies of perceptual learning, however, a change in stimulus location on the retina is accompanied by positional changes of the stimulus in nonretinotopic frames of reference, such as rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
4
29
0
Order By: Relevance
“…However, a recent fMRI study suggested that human MT has a spatiotopic processing component (d’Avossa et al, 2007) and psychophysical evidence from adaptation, perceptual learning and integration studies appear to support this (Melcher and Morrone, 2003; Melcher, 2005; Zhang and Li, 2010; but see Afraz and Cavanagh, 2009; Knapen et al, 2009; Morris et al, 2010). Recently, we conducted a psychophysical study on humans which used a short-term memory for motion task that appeared to corroborate the possibility of spatiotopic processing in area MT (Ong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent fMRI study suggested that human MT has a spatiotopic processing component (d’Avossa et al, 2007) and psychophysical evidence from adaptation, perceptual learning and integration studies appear to support this (Melcher and Morrone, 2003; Melcher, 2005; Zhang and Li, 2010; but see Afraz and Cavanagh, 2009; Knapen et al, 2009; Morris et al, 2010). Recently, we conducted a psychophysical study on humans which used a short-term memory for motion task that appeared to corroborate the possibility of spatiotopic processing in area MT (Ong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gibson (1963, p. 29) defined perceptual learning as '[any] relatively permanent and consistent change in the perception of a stimulus array, following practice or experience with this array'. However, recent psychophysical studies have also suggested that perceptual improvements might be related to changes outside of the visual cortices (Zhang & Li, 2010;: Perceptual learning could be a result of refinement of processing in the decisionmaking and attentional systems. However, recent psychophysical studies have also suggested that perceptual improvements might be related to changes outside of the visual cortices (Zhang & Li, 2010;: Perceptual learning could be a result of refinement of processing in the decisionmaking and attentional systems.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstream view suggests that cortical changes occurring in the early visual cortex, such as the primary visual cortex, (V1) underlie behavioural changes in visual perceptual learning (Karni & Sagi, 1991;Pourtois, Rauss, Vuilleumier, & Schwartz, 2008;Schoups, Vogels, Qian, & Orban, 2001;Schwartz et al, 2002;Walker, Stickgold, Jolesz, & Yoo, 2005;Yotsumoto et al, 2008). However, recent psychophysical studies have also suggested that perceptual improvements might be related to changes outside of the visual cortices (Zhang & Li, 2010;: Perceptual learning could be a result of refinement of processing in the decisionmaking and attentional systems. This idea is supported by neuroimaging studies showing that only the activity pattern in the anterior cingulate cortex tracks changes during perceptual learning (Kahnt, Grueschow, Speck, & Haynes, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…How do we successfully perceive motion in allocentric/spatiotopic coordinates? There is recent psychophysical and fMRI evidence both for (Melcher and Morrone 2003;d'Avossa et al 2007;Ezzati et al 2008;Ong et al 2009;Fracasso et al 2010;Zhang and Li 2010) and against (Boi et al 2011;Wenderoth and Wiese 2008;Knapen et al 2009, Gardner et al 2008) spatiotopic motion processing. It is well accepted that coding visual stimuli in spatiotopic coordinates requires a more complex process than retinotopic coding, since spatial updating mechanisms must take into account the metrics of the upcoming saccade in order to integrate subsequent frames into a coherent percept (Prime et al 2011).…”
Section: Introductionmentioning
confidence: 96%